Fluorescence In Situ Hybridization: a potentially useful technique for detection of microorganisms on mortars - González, M (2015)
This paper discusses the possibilities of applying Fluorescence In Situ Hybridization (FISH) to detect microorganisms on mortars, as this analytical technique has been used in different fields for the detection and identification of individual microbial cells in situ. FISH technique was applied for microbial detection on test and real mortars inoculated with fungal suspensions of S. cerevisae 396 and Nectria sp. A universal eukaryotic probe (EUK516) labelled with fluorescent dye (Cy3) was tested with different cell fixation procedures (4% (w / v) paraformaldehyde or 50% (v / v) ethanol in PBS). Positive results were obtained with FISH detection of Nectria on testing/artificial as well as authentic/historical mortars, which confirms successful application of FISH technique to a new on mortars.